Comparative study on differences in lung parameter between the obese and non obese collegiate sedentary students - Yen, Jessie Kho S’Sia; Bharathi, Mahadevi; B, Arun (Bangladesh Journal of Medical Science, 2018)
Background: Obesity is a chronic and complex disorder which is characterized by an excessive accumulation of body fat that affects the normal healthy body. Obesity will influences functions of various systems in the body. Fat accumulation may influence lung function which might deteriorate respiratory well-being. Studies have identified those obese individuals prone to have respiratory symptoms like dyspnea when compared with non obese individuals. Method: So this study aims to find out the lung parameter differences between the obese and non obese collegiate students. Cross sectional study design which involves 80 collegiate students was selected for this study using non probability sampling method. Based on the BMI the students were classified as Obese and Non obese. Result: 40 students with obesity (Class I) and 40 students were non obese all students were ranged with the age group of 18—32 yrs. Once the consent was obtained from the participants all are asked to do the tasks which include six minute walk test and spirometry. Conclusion: The walking time and the FVC, FEV1/FVC & PEFR values were identified. Inferential statistics were done between the groups and the study shows that there was significant differences exist in the walking time and the FVC, FEV1/FVC values between Obese and Non obese individuals. Bangladesh Journal of Medical Science Vol.17(3) 2018 p.351-354